Allicin ameliorates acute myocardial infarction in rats by modulating calcium homeostasis in cardiomyocytes through the induction of hydrogen sulfide production - Liu, Weiyu; Xu, Shaojun; Wang, Juan; Li, Xinxia; Liu, Ruiting; Zhao, Le; Li, Yikui; Shi, Rongmei; Zhang, Jinyan (Frontiers in Pharmacology, 2025)
BackgroundAcute myocardial infarction (AMI) is a common cardiovascular disease with high morbidity and mortality rates. Allicin, the primary active component of traditional Chinese herbs garlic, has multiple cardiovascular effects. However, the protective effect of allicin on AMI is rare. This study aimed to identify the pathways through which allicin stimulates hydrogen sulfide (H2S) production to regulate calcium ion (Ca2+) homeostasis in cardiomyocytes, thereby contributing to AMI protection.MethodsIn this study, we established an AMI rat model by ligating the left anterior descending branch of the coronary artery to assess the therapeutic effect of allicin. We also investigated its influence on cardiomyocyte Ca2+ homeostasis. To determine the role of H2S production in the effects of allicin, we identified the H2S synthase in healthy rat myocardial tissue and serum and then applied H2S synthase inhibitors to block H2S production.ResultsThe results indicate that allicin significantly enhanced cardiac function, raised H2S levels in myocardial tissue and serum, reduced necrosis tissue size, decreased myocardial enzyme levels, and improved myocardial pathological changes. Surprisingly, allicin also notably increased H2S synthase levels. These findings suggest that allicin shields AMI rats by stimulating H2S production, acting both as a direct H2S donor and indirectly boosting H2S synthase expression. Furthermore, allicin enhanced Ca2+ homeostasis in cardiomyocytes by improving cardiomyocyte contraction kinetics and regulating the function and expression of key proteins related to Ca2+ transport in cardiomyocytes. The effect of allicin on Ca2+ homeostasis was partially decreased but not entirely abolished when H2S production was inhibited using H2S synthase inhibitors PAG and AOAA. This suggests that while the impact of allicin is strongly associated with H2S, additional independent mechanisms are also involved.ConclusionOur study presents novel evidence demonstrating that allicin modulates Ca2+ homeostasis in cardiomyocytes by stimulating H2S production, thereby conferring protection against AMI. Furthermore, the protective effects of allicin are partly mediated by, but not solely reliant on, the generation of H2S. These findings not only provide mechanistic insights into the anti-AMI effects of allicin but also underscore its therapeutic promise.